Stability and plasmatic protein binding of novel zidovudine prodrugs: Targeting site ii of human serum albumin - Schenfeld, Esteban Martin (2018)
Despite its vastly demonstrated clinical efficacy, zidovudine (AZT) exhibits several suboptimal pharmacokinetic properties. In particular, its short plasmatic half-life (t1/2 ~ 1 h) is related to its low bound fraction to whole plasmatic proteins and in particular to human serum albumin (HSA). The design of prodrugs constitutes a promising strategy to enhance AZT pharmacokinetic properties, including its affinity for HSA. Recently, we reported the synthesis and chemical stability evaluation of three novel prodrugs of AZT obtained by derivatization with dicarboxylic acids (1–3). In this work, we present the design, synthesis and evaluation of chemical and enzymatic stabilities of a novel series of double prodrugs of AZT obtained by derivatization of 1–3 with a methylated l-phenylalanine moiety (4–6). In addition, the plasmatic protein binding properties were studied both by experimental and theoretical techniques. Prodrugs 4–6 were found to be relatively stable at pH 7.4 (t1/2 between 4.1 and 57.8 h), while also demonstrated adequate stabilities in human plasma at 37 °C (t1/2 between 1.0 and 2.1 h). Also, prodrugs 4–6 were able to regenerate AZT at a rate that depended on the length of the alkyl chain in 1–3. Additionally, 4–6 exhibited a significantly increased binding to plasmatic proteins (between 52.1 and 72.5%) with respect to AZT (12%) and 1–3 (between 26 and 34%). It is noteworthy that the displacement experiments with HSA site I and II markers, demonstrated that 4–6 bound to a different site than that of AZT and 1–3. Molecular modeling studies (i.e. molecular docking and free energy of binding analysis) were applied to shed light at an atomistic level on the pharmacodynamic properties driving the interaction of 4–6 with HSA. Overall, the present work provides a state of the art contribution to the design and development of novel prodrugs of AZT with optimized pharmacokinetic properties.